2000
DOI: 10.1111/j.1572-0241.2000.03187.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Autoimmune-Related Pancreatitis

Abstract: Autoimmune mechanism may be involved in some patients with idiopathic pancreatitis associated with hypergammaglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(48 citation statements)
references
References 23 publications
5
40
0
3
Order By: Relevance
“…3,16 However, neither case in this survey had clinical or pathological features to suggest pancreatitis or other lesions of IgG4-SD, and both patients had long histories of complicated diabetes by the time of their biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 However, neither case in this survey had clinical or pathological features to suggest pancreatitis or other lesions of IgG4-SD, and both patients had long histories of complicated diabetes by the time of their biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Typing of the inflammatory duct-associated cells revealed CD4 þ and CD8 þ T cells to be the most common. 6,90 Increased numbers of these T cells bearing HLA-DR were also found in the peripheral blood. 107 Subtyping of the CD4 þ cells according to their cytokine production profiles revealed a predominance of CD4 þ Th1 cells over Th2 cells in some cases, 107 similar to what has been reported in Sjö gren's disease 108 and primary sclerosing cholangitis.…”
Section: Pathogenesismentioning
confidence: 94%
“…9,11 Patients with autoimmune pancreatitis may have autoantibodies such as antinuclear, antilactoferrin, antismooth muscle and anticarbonic anhydrase II antibodies. 89,90 More recently it has been observed that IgG4 levels are commonly elevated in patients with autoimmune pancreatitis. 91 Elevated IgG4 levels have been used to correctly classify patients with pancreatic masses.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…En aquel momento este equipo investigador considera la hipótesis de que estas enfermedades constituyan la manifestación, en diferentes órganos, de una reacción autoinmune frente a un antígeno común expresado en las células de los conductos de los órganos exocrinos y que la anhidrasa carbó-nica II era el candidato a ser este antígeno diana (18). En los siguientes años fueron publicados varios estudios clí-nicos donde se analizaba el valor diagnóstico de la presencia de estos autoanticuerpos, llegándose a la conclusión de su escasa especificidad (15,18,19), habiéndose encontrado en otras afecciones como las pancreatitis alcohólicas, sín-drome de Sjögren primario, lupus eritematoso, endometriosis, artritis reumatoide, hepatitis viral, etc., por otro lado se constató su ausencia en casos con pancreatitis autoinmune comprobada, calculándose que estos anticuerpos están presentes en sólo el 50% de los casos (20,26,41). Ello, unido al hecho de que la IgG4 sérica se encuentra aumentada en esta enfermedad de manera más sensible y específica ( Fig.…”
Section: Manifestaciones Biológicasunclassified